DUAL CONCEPTION OF MACHINATION IN HEIDEGGER’S PHILOSOPHY OF TECHNOLOGY - Čapanauskas, Tadas (Problemos, 2017)
The article deals with the dual machination conception in Martin Heidegger’s philosophy of technology. First conception is related to the destruction of Western metaphysics (Destruktion) and its culmination reflected in the realm of modern technology. But first of all, Heidegger presents machination as opening sway of being in the first beginning (ersten Anfang). Machination causes the foundation of μετά motion, which is showing to the constant aspiration of the transcendence and “technical” opening of beings, but the “capacity”of machination still lies implicitly in Greek metaphysics. Explicitly machination appears only in the realm of modern technology. Slightly different understanding of machination we can find in Heidegger’s Black Notebooks (Schwarze Hefte), written between the year 1931 to 1938. In those notebooks, philosopher represents the whole modern era as machination. So the article aims to highlight the connection of these two Heideggerianconceptions that refers to the growth of machination power (Macht) over reality.
Keywords: Machenschaft; machination; technology; establishment; Gestell; power